Nursing students’ perception on their clinical learning environment - Ahmad, Norfadzilah (IIUM Press, 2017)
Quality in academia and effective clinical learning are important factors in nursing education. Positive perception on clinical environment provides opportunity for students to gain appropriate knowledge in caring of the patient comprehensively, develop clinical judgement and critical thinking skills. The aim of an institution is to provide the best and highest quality of clinical education for the students; meaningful clinical experiences ensure competent nurse in the future. The aim of this study was to measure Kolej Islam Sains & Teknologi (KIST) final year nursing students’ perception on their clinical learning environment. This research was cross sectional study combining both quantitative and qualitative methods. The Clinical Learning Environment Scale (CLES) inventory with 5 domains was administered to 175 final year Diploma of Nursing students at KIST. The items mean scored below 3 were considered as problematic areas. The areas were further explored via focus group discussion (n=12). The overall mean score on the 23 items CLES inventory was 78.5 out of a maximum 115. Out of the 5 domains, the highest mean score was on domain 4 (Student Satisfaction), followed by Domain 1(Staff – student relationship), Domain 3 (Patient student relationship) and finally Domain 5 (Hierarchy and Ritual). All domain scores were toward positive directions. Only one domain showed negative perception which was Domain 2 (Nurse Manager Commitment). Six items from different domains scored less than 3. All these items were identified and explored to find underlying causes for the lower score through focus group discussion and result varied from students’ in different semester group. This study, combination of Quantitative and Qualitative method were used to investigate perception of nursing students regarding clinical learning environment. This study showed that, positive perception of the nursing students toward clinical learning environment is an important factor influencing their learning process. It is recommended that the responsible authorities of nursing institutions should focus on developing positive clinical learning environment to ensure successful clinical teaching and learning can be achieved.